Afluentes e confluências: O desaguar dos sentidos na arte/educação inclusiva - Bacurau, Caroline Moreira (2017)
The following research covers Formal Education in Visual Arts with a focus on Inclusive Education stemming from propositions that emphasize multi-sensory in the Visual Arts. This specific field of research was performed in Petrolina, in the state of Pernambuco, a city on the margins of the São Francisco River, where I performed a research-action at Vivência Centro Educacional, a private school. The research was performed with eight classes between the 6th and 9th year of Middle School, two classes in each school year. The field activities were performed with the assistance of the resident Arts teacher. Works by Hélio Oiticica, Lygia Clark and Ernest Neto- three contemporary brazilian artists, were used as the main references in the classroom activities; regarding the concept of School Inclusiveness, I based myself on Carvalho (2004) and Pacheco (2007); regarding methodological guidance in the teaching of Visual Arts, I resorted to Ana Mae Barbosa’s “Abordagem Triangular.” Over the year of 2015, the researched focused on gathering information on the methods used for inclusive education in the region and the educators’ conceptions of them; in 2016 the field activities were performed and the obtained results were analyzed. Inclusive education proved itself to be a realistic possibility, wherein the effectiveness of actions is connected to the strengthening of support networks: the community created by each class, the relations between family and school, the realizations of adaptations by schools to lower the learning barriers, and the recognition of each student’s individuality. In the teaching of Visual Arts, the focus must be the practice on involving reading and individual creation as well as collective work, though it is necessary that these practices exhibit a purpose for the students and promote meaningful experiences.